KEPRIBADIAN TOKOH UTAMA NOVEL MANUSIA DAN BADAINYA KARYA SYAHID MUHAMMAD SERTA RELEVANSINYA DALAM PEMBELAJARAN DI SMA - Erdita Nur Rahmawati; Hasan Suaedi; Eka Nova Ali Vardani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
The study aims to analyze the healthy personality of the main character in the Manusia dan Badainya novel and to describe its relevance in high school studies. The methods involve a type of qualitative work. Data collection uses reduction techniques. The source of the data is the Manusia dan Badainya novel by Syahid Muhammad novel that released on 2022. The background is to identify healthy personality phenomena of the main character in the Manusia dan Badainya novel. The results of are that 13 physiological data found on the main character in the Manusia dan Badainya novel. There are consist of some details, the physiological needs eat and drink as 6 data, physiological needs of residence and rest are 3 data each of them, and the physiological needs of clothing as 1 data. The conclusion is the main character in the novel fulfill one of the requirements of a healthy personality according to maslow's theory of personality. A healthy personality consisting of the dominant physiological needs of the main character is the physiological needs of eating and drinking. This analysis has relevance to high school literature, especially at phase F in the free curriculum.